Implications of Withaferin A for the metastatic potential and drug resistance in hepatocellular carcinoma cells via Nrf2-mediated EMT and ferroptosis. (2nd January 2023) - Zhang, Yigang; Tan, Yi; Liu, Shuangchi; Yin, Hongxiang; Duan, Jiakang; Fan, Longfei; Zhao, Xiangyang; Jiang, Bowen
Abstract: Hepatocellular carcinoma (HCC) constitutes a major global health threat due to the high incidence and mortality. Sorafenib is known as the first-line medication for advanced HCC; however, it only extends the limited benefit for HCC patients as the development of acquired resistance. Withaferin A exerts broad pharmaceutical applications in several cancers. However, its effects on HCC cell metastatic potential and sorafenib resistance remain elusive. Here, we corroborated that Withaferin A greatly restrained cell viability, invasion, vasculogenic mimicry (VM) formation, and VE-cadherin levels in HepG2 and SNU449 cells. Moreover, Withaferin A sensitized sorafenib (SR)-resistant HCC cells to sorafenib. In striking contrast to the parental cells, lower ferroptosis was observed in SR-resistant cells as the lower ROS, MDA, and higher intracellular GSH levels in SR-resistant cells. Of interest, Withaferin A enhanced ferroptosis in SR-resistant cells, which was reversed by ferroptosis antagonist liproxstation-1. Notably, Withaferin A elevated Keap1 expression to mitigate Nrf2 signaling activation-mediated epithelial to mesenchymal transition (EMT) and ferroptosis-related protein xCT expression. Importantly, blockage of the Keap1/Nrf2 signaling overturned Withaferin A-evoked ferroptosis and facilitated sorafenib resistance. In addition, knockdown of Keap1 antagonized the inhibitory efficacy of Withaferin A on HCC cell viability, invasion, and VM formation. Consequently, Withaferin A may attenuate the metastatic potential and sorafenib resistance by regulating Keap1/Nrf2-associated EMT and ferroptosis. Thus, Withaferin A may serve as a promising agent for HCC therapy, especially for advanced HCC.